CANDI GUNUNG GANGSIR AND THE CHARACTER OF THE EARLY EAST JAVANESE ARCHITECTURE - Peter R. Hoffmanns (Balai Arkeologi Yogyakarta, 1987)
In this contribution I would like to draw some attention to a period which is widely considered to be a black hole or a white spot, in any case